Soil invertebrates in southern Brazilian Araucaria forest - grassland mosaic: differences between disturbed and undisturbed areas - Frainer,André (2009)
Soil invertebrate distribution in Araucaria forest, grassland and edge habitats was studied in both disturbed and undisturbed areas in southern Brazil. Mean-density and taxa compositions were verified. Invertebrate densities differed between grassland and the other two habitats in the undisturbed area but not across the disturbed one. At the disturbed area taxa differed between the grassland and the other two habitats. The undisturbed area, on the other hand, presented taxa differences only between the grassland and the forest habitats. Acari, Arachnida and Collembola were the most sensitive taxa for detecting differences across habitats in both areas. At the disturbed area, these taxa presented densities lowering from the forest to the grassland. At the undisturbed area the same taxa increased from the forest to the grassland. Coleoptera and Formicidae (Insecta) presented no difference between habitats at the studied taxonomic level.